Kekayaan Intelektual dalam Perspektif Ekonomi Islam - Musyafa, M (Faculty of Shariah and Law, 2013)
Intelectual rights in Indonesia is regulated comprehensively, whereas Islamic texts do not explain it in a specific way. Rights in Islam are a divine gift as guidance in determining the laws of sharia. Every person is obliged to respect the rights of others, and it is obviously forbidden to destroy or trample these rights. Moreover, the owner of the rights should use it properly without causing harm to others. In economic perspective, a person is prohibited trading a thing that is not belonging to him/her, causing violation of copyright laws. Intelectual works of a person is regarded as the intellectual property. Islam appreciate these rights in qualifying the rights attached to its owner.DOI: 10.15408/aiq.v5i1.2108